The Relationship between Individual Characteristics and Work Safety with Work Stress in Workers at PT Pertamina Zone 1 Jambi Field in 2022 - Widi Fatchurrachman P; RD. Halim (PT FORMOSA CENDEKIA GLOBAL, 2023)
An unsafe workplace can cause anxiety at work which is one of the symptoms of work stress, the aim of this research is to determine the relationship between age, length of work and work safety with work stress. This type of research is quantitative observational cross sectional study design. The research population is production workers at PT Pertamina Zone 1 Field Jambi, totaling 36 workers as well as being the research sample. Data analysis used the Chi-Square statistical test. The results showed that the prevalence of workers with old age was 58.3%, long service life was 61.1%, work safety was not good at 38.9% and those who experienced work stress were 77.8%. The results of the bivariate analysis showed that there was a relationship between age (p-value=0.046, PR=1.508), years of service (p-value=0.036, PR=1.591), work safety (p-value=0.013, PR=1.571) and work stress.